2020
DOI: 10.3233/mnm-200413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synbiotic supplementation on matrix metalloproteinase enzymes, quality of life and dietary intake and weight changes in rectal cancer patients undergoing neoadjuvant chemoradiotherapy

Abstract: BACKGROUND: Probiotic/synbiotic has the important role of in altering intestinal bacteria, reducing inflammation and improvement of intestinal diseases. OBJECTIVE: We aimed to investigate the effect of synbiotic supplementation on matrix metalloproteinase (MMP) enzymes, hs-CRP, quality of life, dietary intake and weight changes in rectal cancer patients undergoing neoadjuvant chemoradiotherapy (CRT). METHODS: In this study, 46 rectal cancer patients were recruited. Patients were allocated to the synbiotic (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Following the above inclusion and exclusion criteria, 507 articles (ongoing studies, unexpectedly terminated trials, noncancer patients, not oral probiotic use, in vitro studies, nonchemotherapy studies, and reviews) and 38 duplicate articles were removed after carefully reading their titles and abstract, leaving only 51 articles. After reading the remaining articles, 39 additional studies were further excluded because of that 12 studies did not include cancer patients or they were not receiving chemotherapy (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), two did not include oral probiotic use (38,39), 20 had no record of diarrhea or oral mucositis in patients (40-59) (18 of them did not include diarrhea or oral mucositis indicators (40)(41)(42)(43)(44)(45)(46)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and the other two studies only recorded the frequency of diarrhea or oral mucositis rather than the number of patients who had the adverse reactions (47, 48)), and five were not randomized controlled trials (60)(61)(62)(63)(64). Finally, 12 articles were selected for the meta-analysis.…”
Section: Literature Screening and Population Characteristicsmentioning
confidence: 99%
“…Following the above inclusion and exclusion criteria, 507 articles (ongoing studies, unexpectedly terminated trials, noncancer patients, not oral probiotic use, in vitro studies, nonchemotherapy studies, and reviews) and 38 duplicate articles were removed after carefully reading their titles and abstract, leaving only 51 articles. After reading the remaining articles, 39 additional studies were further excluded because of that 12 studies did not include cancer patients or they were not receiving chemotherapy (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), two did not include oral probiotic use (38,39), 20 had no record of diarrhea or oral mucositis in patients (40-59) (18 of them did not include diarrhea or oral mucositis indicators (40)(41)(42)(43)(44)(45)(46)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and the other two studies only recorded the frequency of diarrhea or oral mucositis rather than the number of patients who had the adverse reactions (47, 48)), and five were not randomized controlled trials (60)(61)(62)(63)(64). Finally, 12 articles were selected for the meta-analysis.…”
Section: Literature Screening and Population Characteristicsmentioning
confidence: 99%
“…The year of publication ranged from 2007 to 2023, where approximately 70% of the studies were published in the last 10 years. In terms of geographic localization the included studies are from China (n=6) ( 34 39 ), Turkey (n=2) ( 40 , 41 ), Slovenia (n=2) ( 42 , 43 ), Japan (n=2) ( 44 , 45 ), Greece (n=2) ( 46 , 47 ), Brazil (n=2) ( 48 , 49 ), Iran (n=2) ( 50 , 51 ), Malaysia (n=1) ( 52 ), Finland (n=1) ( 53 ), Sweden (n=1) ( 54 ), Slovakia (n=1) ( 55 ), Republic of Korea (n=1) ( 56 ) and Bosnia and Herzegovina (n=1) ( 57 ). There were a total of 2204 participants, 1139 in the intervention groups and 1065 in the control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Species of the Lactobacillus, Bifidobacterium and Enterococcus genera were the most commonly used for the probiotics or synbiotics intervention. Placebo was used for the control group in 18 of the studies ( 34 42 , 46 50 , 52 , 54 56 ) while the other 6 used standard care treatment ( 43 45 , 51 , 53 , 57 ). Characterization of these studies is shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, another clinical study demonstrated the effect of synbiotic supplementation on colorectal cancer patients ( n = 46) undergoing chemotherapy. The study reported a slight decrease in the mean symptom score for diarrhoea in the synbiotic group when compared to the placebo group where it increased significantly [ 134 ]. More recently, a randomised clinical trial found that the administration of synbiotics prevented bacteremia and reduced gastrointestinal toxicities, including diarrhoea in oesophageal cancer patients ( n = 42), for those receiving chemotherapy [ 135 ].…”
Section: Synbiotic Therapy To Alleviate Chemotherapy-associated Symptomsmentioning
confidence: 99%